Factors Influencing Motivation for Home Blood Pressure Monitor in Elderly with Hypertension - Siswati; Sari, Desy Siswi Anjar; Dianita, Eka Mei; Maryati, Heni; Praningsih, Supriliyah; Nurmalisyah, Fitri Firranda (Al-Hijrah Indonesia, 2024)
Background: Home blood pressure measurement by hypertensive patients is still very low, even though it is important to help control complications and manage therapy. Aims: This study aims to analyze the factors that can influence the motivation of sufferers to measure blood pressure at home. Method: This study used an explanatory design, a sample of 30 respondents with a purposive sampling technique. Data was collected using a questionnaire and analyzed using common factor analysis. Results: The results of the statistical test obtained the KMO and Barlett Test p values <0.000 and the MSA value> 0.5, which indicates that the variables can be continued for further analysis to determine the most dominant factors by looking at the eigenvalue> 1, with the final results of the five variables (Education, occupation, knowledge, social support, and disease conditions) studied only three variables met the statistical test criteria two variables that did not meet the test, namely Education, and occupation. Conclusion: Three main variables influence the motivation of the elderly to measure blood pressure at home, namely knowledge, social support, especially health workers, and disease conditions. It is hoped that health workers will provide advice on the importance of measuring blood pressure at home.